PENGEMBANGAN SISTEM E-VOTING DENGAN PROTOKOL TWO CENTRAL FACILITIES MENGGUNAKAN FINGERPRINT SEBAGAI OTENTIKASI VOTER - Sikki, Muhammad Ilyas; Guritman, Sugi; Rahmawan, Hendra (JREC (Journal of Electrical and Electronics), 2013)
The e-voting system which developed using two central facilities protokol consist of three componentthat is voting machine as client for interaction with voter, central legitimization agency (CLA) asserver voter authentication, and central tabulating facility (CTF) as server for result recapitulationvoter vote count. Research in this thesis just focused to voter authentication process on votingmachine toward database of voter that stored in CLA with using fingerprint biometric technology.Fingerprint biometric technology used for voter registration process, voter verification process, andvoter authentication process who will doing election. Registration process for acquire voterfingerprint image database, verification process to be sure voter database can be verificated or not,and authentication process for voter authorization who can be permitted or not by system give of votein election.Key words : E-voting, voter, authentication, fingerprint